Images and stability of black hole with cloud of strings and quintessence in EGUP framework - Shahid Chaudhary; Muhammad Danish Sultan; Adnan Malik; Atiq ur Rehman; Ali Övgün; Ayman A. Ghfar (Nuclear Physics B, 2024)
We consider black holes with quintessence matter and cloud of strings to study shadow, optical appearance and stability by using the extended generalized uncertainty principle. We first evaluate the relations for modified Hawking temperature, heat capacity, equation of state and remnant mass for the considered model and then plot these relations in order to analyze the quantum correction effects on the stability of the black holes. In the visual plot of specific heat, we observe critical regions where the black hole transitions from being thermodynamically stable to unstable and vice versa. Moreover, we also observe that the regions of stability and instability are not uniform across, suggesting that extended generalized uncertainty principle plays a vital role in thermodynamic properties. We also investigate the silhouette and optical properties of the Lovelock black hole, particularly analyzing illumination with two theoretical models of static accretion. We observe that different values of Lovelock coupling constants significantly influence the size of image and intensities of the black hole.